Effects of Single Probiotic- and Combined Probiotic-Fermented Milk on Lipid Metabolism in Hyperlipidemic Rats - Wa, Yunchao; Yin, Boxing; He, Yong; Xi, Wenbo; Huang, Yingping; Wang, Chunlei; Guo, Feixiang; Gu, Ruixia (Frontiers in Microbiology, 2019)
Previous findings have shown that probiotics exert positive effects on hyperlipidemia by lowering serum lipid and improving lipid profile. To explore the mechanism of probiotic fermented milk improving lipid metabolism, the transcription of genes regulated by Liver X receptors (LXR), 5' -AMP -activated protein kinase (AMPK) and farnesoid X receptor (FXR) which play an integral role in lipid metabolism was investigated in hyperlipidemic rats. Compared with high-fat group, the probiotics fermented milk intervention significantly lowered the level of total cholesterol (TC) and total triglyceride (TG) in rats’ serum and viscera (P<0.05), and significantly increased the level of total bile acid (TBA) in rats’ liver and small intestine (P<0.05). The results of qPCR showed the probiotics ameliorated the level of TC in rats by activating the transcription of genes on the LXRs axis, which promoted TC reverse transport and increased the conversion of TC to bile acids. The level of TG in hyperlipidemia rats was ameliorated by inhibiting the transcription of genes of ChREBP and activating the transcription of genes of PPARα. The regulation of lipid metabolism related gene transcription by single probiotic (Lactobacillus.rhamnosus LV108) fermented milk was more effective than that by combined probiotic (Lactobacillus rhamnosus LV108, Lactobacillus casei grx12 and Lactobacillus fermentum grx08) fermented milk (P < 0.05)